An analysis code mixing among judges’ commentary in Indonesia Next Top Model - Alfia Ayu Apriliantina; Yuli Kuswardani (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2022)
Code-mixing is the simultaneous use of statements or utterances in two different languages; the switch from one language to the other happens within a single sentence. There are three types of code mixing and seven reasons for code mixing. This is about phenomena code mixing that occurs in Indonesia Next Top Model. The objectives of this study are to categorize different types of code mixing and to explain why judges in Indonesia Next Top Model employ code mixing. This study used qualitative descriptive analysis as its research approach. The four judges of Indonesia Next Top Model are the subject of this study. The findings of this study are: The research's most prevalent code-mixing is 31 items of congruent lexicalization, with a percentage of 47,69, and the study's least dominant code-mixing is 16 items of insertion, with a percentage of 24,62. Then the reason of code mixing the most dominant reason is talking about a particular topic, the researcher finds 36 data used this reason and the lowest reason is interjection (insert sentence fillers or sentence connector) in this research 1 data is used this reason.